A new high‐order fluid solver for tokamak edge plasma transport simulations based on a magnetic‐field independent discretization. Issue 6 (8th January 2018) - Giorgiani, G.; Camminady, T.; Bufferand, H.; Ciraolo, G.; Ghendrih, P.; Guillard, H.; Heumann, H.; Nkonga, B.; Schwander, F.; Serre, E.; Tamain, P.
Abstract : Our global understanding of the power exhaust in tokamaks, and its implications for both steady‐state and transient heat loads on divertor and limiter PFCs, is still poor. In transient situations in particular, such as during start‐up or control operations, the evolution of particles and heat fluxes is little known, although they are critical for the safety of the machine. The heat load is largely determined by the physics of the Scrape‐Off Layer (SOL), and therefore, it depends to a large extent on the geometry of the magnetic surfaces as well as on the geometry of wall components. A better characterization of the heat exhaust mechanisms is therefore required to improve the capabilities of the transport codes in terms of geometrical description of the wall components and in terms of the description of the magnetic geometry. For transient simulations, it becomes crucial to be able to deal with non‐stationary magnetic configurations. In particular, avoiding expensive re‐meshing of the computational domain is mandatory. In an attempt to achieve these goals, we propose a new fluid solver based on a high‐order hybrid discontinuous Galerkin (HDG) finite element method. Capitalizing on the experience acquired in the development of the SOLEDGE2D‐EIRENE transport model, we propose to study edge plasma transport in the frame of a reduced model (but containing most of the challenging issues regarding accurate numerical simulations) based on electron density and parallel momentum. The code is verified using manufactured solutions and validated using well‐referenced simulations in a realistic WEST geometry. Finally, we demonstrate how the particle fluxes at the wall vary in our model when the magnetic equilibrium evolves in time, particularly during the equilibrium construction skip from a limiter configuration to a diverted one at the beginning of the operation.